2016
DOI: 10.1002/ajhb.22869
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and body composition in urban and rural schoolchildren: A cross‐sectional study in San Rafael, Mendoza (Argentina)

Abstract: Children from San Rafael presented differences in nutritional condition and body composition associated with pronounced socio-environmental heterogeneity. Thus, we could observe a gradient from the "high urban" group, with better social, economic, and sanitation conditions and at the same time a more obesogenic environment to the "impoverished urban" and "rural" groups, whose vulnerability reflected a higher prevalence of child undernutrition and the association with excess weight and reduced muscle mass. Am. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…The prevalence of undernutrition (10.2%) was high compared to other provinces of Argentina. (37,38) Moreover, prevalence of underweight (3.5%) and stunting (9.3%) showed that children experience serious nutritional deficiencies as a consequence of the limited socio-economic conditions of their families, inadequate hygiene practices and sanitation. This scenario was reflected in undernourished children who were the most infected, especially by Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of undernutrition (10.2%) was high compared to other provinces of Argentina. (37,38) Moreover, prevalence of underweight (3.5%) and stunting (9.3%) showed that children experience serious nutritional deficiencies as a consequence of the limited socio-economic conditions of their families, inadequate hygiene practices and sanitation. This scenario was reflected in undernourished children who were the most infected, especially by Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…In Argentina, different populations are going through a nutritional transition, with marked differences among provinces, regions, and socioeconomic conditions (Bergel Sanchís, Cesani, & Oyhenart, ; Garraza, Cesani, Navone, & Oyhenart, ; Lomaglio, ; Oyhenart et al, ). However, data for the province of Tucumán are not currently available.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al [22] noted that the lower urban malnutrition occurrence was due to more favourable socioeconomic conditions such as women's education and status, presence of water sanitation as well as household income. Similarly, Khambalia et al [23], Garraza [24], and Yadav [11] all found that the prevalence of underweight was higher in rural area compared to urban area. Difference in socioeconomic status as well as dietary patterns were attributed as the reason of this disparity [18].…”
Section: Discussionmentioning
confidence: 87%
“…Difference in socioeconomic status as well as dietary patterns were attributed as the reason of this disparity [18]. A more detailed study was done by Garraza [24] which found that a better and more favorable socio-environmental living conditions such as good quality housing, accessibility of public services and buying power of families permitted improved food access in living household, thus, reduced the prevalence of malnutrition.…”
Section: Discussionmentioning
confidence: 99%